Manajemen Kearsipan Digital dalam Upaya Meningkatkan Mutu Sistem Penyimpanan Dokumen Kepegawaian di Kota Banda Aceh: Hambatan dan Tantangan - Adinda Aulia; Rudi Kurniawan (Asia-Pacific Journal of Public Policy, 2022)
The quality of staffing documentation stored electronically at the Aceh Public Works and Spatial Planning Office of Banda Aceh City is unsatisfactory. This study aims to find out how the process of managing archives management improves the quality of the employee document storage system by using electronics as a storage medium. The data techniques employed were observation, interviews and documentation. The type of this research is qualitative. The results of this study can be reported that the obstacles that occur in the Aceh Public Works and Spatial Planning Office of Banda Aceh City are: (1) Lack of understanding of the importance of archives by members of the organization; (2) It has not been carried out or cultivated regarding the guidelines for borrowing archives so that every employee borrows files without clear regulations; (3) There is no planning regarding the shrinkage of archives so that the libraries are piling up and are no longer accommodated. It is hoped that government agencies will be able to improve the quality of documentation storage systems using electronic media and utilize employees who are reliable and capable of operating computers properly.